PELATIHAN PEMANFAATAN MICROSOFT OFFICE UNTUK MENDUKUNG KOMPETENSI DIGITAL MAHASISWA - La Ode Takbir; Aulia Jannatul Ma’wa; Idawati Idawati; Resty Resty; Achmad Ramadhan; Zila Razilu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Students' digital competence is a crucial aspect in supporting the quality of scientific writing in higher education, particularly in utilizing Microsoft Office features that are not yet optimally utilized. This study aims to describe the implementation of Microsoft Office training and analyze its effectiveness in improving the digital competence of students in the Information Technology Education Study Program at Muhammadiyah University of Kendari. The study used a qualitative descriptive approach with purposive subject selection. Data were collected through participant observation and visual documentation that recorded participants' involvement and practice using Microsoft Word and Mendeley in managing academic documents. Data analysis was conducted through stages of reduction, grouping, and interpretation based on digital competence indicators. The results indicate that the training improved students' abilities in formatting documents, creating automatic citations and bibliographies, and systematically managing digital references. The demonstration and hands-on approach proved effective in improving students' understanding and accuracy in scientific writing. The study's conclusions indicate that Microsoft Office training positively contributed to improving digital competence and the quality of students' scientific work.